PENERAPAN TEKNOLOGI PENGGUNAAN RUMPUT LAUT SEBAGAI BIOFILTER ALAMI AIR TAMBAK UNTUK MENGURANGI TINGKAT SERANGAN PENYAKIT PADA UDANG VANNAMEI (Litopenaeus vannamei) - Rahmaningsih, Sri (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Fish farmers in the Tuban district mainly vannamei shrimp farmers face tough environmental conditions for shrimp growth, this is caused because of the large industrial district of factories such as Tuban PT Semen Gresik, TPPI plant located in the north sea of Tuban where waste can affect the quality pond water either directly or indirectly. Including shrimp farmers in the village Kenanti, Tambakboyo district and almost all farmers are along the northern coast of Tuban is predicted to feel the effects of contamination originating from the sea, not to mention emanating from the pond itself (waste internal), so natural that the current level of success in aquaculture, especially shrimp vannamei shrimp is very low. The success rate in vannamei shrimp culture, especially in intensive shrimp culture is largely determined by the quality of water used in cultivation and also the technology that has been used. Use of seaweed as a natural biofilter in vannamei shrimp culture is a simple technology that is easy to be implemented. Seaweed is a plant that absorbs water degradation of organic material for growth, thereby reducing the risk of rising water of organic material that would be required to maintain shrimp. And brightness temperature greatly affect the success of a biofilter Iaut grass because the two components will be the rate of photosynthesis of algae and the rate of absorption of organic materials. From the approach used in the implementation of this program is to disseminate the application of technology use seaweed as a natural biofilter at a group of farmers in sub distric of Tambakboyo through training, then held a pilot pond so fish farmers in adopting this technology can be more easily understood.